Cabazitaxel versus docetaxel for treatment of metastatic castrate refractory prostate cancer. Issue 6 (18th June 2022) - James, Nicholas D.; Ali, Ayesha; Pope, Ann; Desai, Amisha; Ford, Daniel; Stevenson, Robert; Zarkar, Anjali; Pirrie, Sarah; ,
Abstract: Objectives: To assess cabazitaxel versus docetaxel re‐challenge for the treatment of metastatic castrate refractory prostate cancer (CRPC) patients previously treated with docetaxel at inception of primary hormone therapy. Patients and Methods: The CANTATA trial was a prospective, two‐arm, open‐label, phase II study conducted in eight UK centres. Patients over the age of 18, with histologically proven, metastatic prostate cancer who had been previously treated with up to 6 cycles of docetaxel as part of the STAMPEDE trial (or treated with the same drug outside of the trial at primary diagnosis) and had a performance status (PS) of 0–2, were eligible. Patients who progressed during primary treatment with docetaxel or had received prior systemic chemotherapy were excluded. Cabazitaxel (25 mg/m 2 ) or docetaxel (75 mg/m 2 ) was administered via intravenous infusion every 3 weeks with oral prednisolone (10 mg) for up to 10 cycles, until disease progression, death or unacceptable toxicity. The primary outcome was clinical progression‐free survival (PFS) as defined by either date of pain progression, date of a cancer‐related skeletal‐related event, or date of death from any cause. Analyses were by intention to treat. EudraCT number: 2012‐003835‐40 Results: Between 7 March 2013 and 4 January 2016, 15 patients with a median age of 70 years (range 54–76) were recruited; seven received cabazitaxel, eight docetaxel. The study was halted due to slow accrual. The median clinical PFS time in the cabazitaxel group was 6.2 months compared with 8.4 for the docetaxel group (95% confidence intervals were not reached due to the small number of patients). A total of 13 serious adverse events were reported. Conclusion: Due to the low number of patients recruited, meaningful comparisons could not be made. However, toxicity was in line with known outcomes for these agents, demonstrating it is feasible and safe to deliver chemotherapy to men relapsing with CRPC after upfront chemotherapy.